Pengelolaan arsip di media massa radio global 101.0 fm Palembang - Yogi Andrianza (UIN Sumatera Utara, 2018)
This article aims to find out an overview of archive management on Global Radio 101.0 FM. By knowing the position, the existence of an archive processing unit at Global Radio 101.0 fm Palembang, and the types of archives stored at Global Radio 101.0 fm Palembang, as well as the archive management system at Global Radio 101.0 fm Palembang. Based on the findings of the authors through observation and interviews that archival management in Radio Global 101.0 FM does not apply archive management in accordance with the provisions contained in the law. Because it does not have a special archive unit and management is still incorporated in the administrations system a processed by a student who is carrying out his lecture that has no background in archival so that the management of the archive on Radio Global 101.0 FM has not been properly implemented. Keywords: archive management, administration, global radio 101.0 fm, radio archive